Motion Control of Industrial Robot with Series Two-link Manipulator Considering Joint Nonlinear - Jun Zhang; Honglong Xu (Jixie chuandong)
At present， the main nonlinear factors that lead to the trajectory tracking error of multi-axis industrial robots are the joint nonlinearity on each axis and the dynamics coupling effect between different axes. For this， a motion control method for industrial robots is proposed， which considers the joint nonlinearity in a series of two-link manipulators. The kinematics and dynamics model of the manipulator is constructed， and a parametric modeling method is proposed. The nonlinear stiffness and friction force of the connecting rod are directly identified as joint nonlinearity. The method is applied to the series two-link manipulator of a typical multi-axis industrial robot with low-frequency vibration characteristics and important influence on trajectory performance. The motion state of the serial double-link manipulator reproduced， the validity of the method is verified by numerical simulation and experimental comparison. Two control schemes， feedback closed-loop control with variable notch filter and two-degree-of-freedom control with dynamic feed-forward compensation are adopted to improve the performance of trajectory tracking and residual vibration suppression. Combining four different motion forms， the experimental study is carried out and compared with the conventional PI trajectory tracking control method. The results show that the two-degree-of-freedom control scheme with identifiable two-link dynamics model and feedback loop with variable notch filter can improve the trajectory tracking and residual vibration suppression performance.